Ius primae noctis? the wedding godfather and some archaic sexual customs in romanian traditional culture - Oișteanu, Andrei (Archaeus, 2012)
This study represents a chapter from my forthcoming book, Sexuality and Society: History, Religion, and Literature. In this paper, I attempt to present a series of arguments that could prove the existence of a special role played by the wedding godfather in the archaic and traditional Romanian culture. This role may be that of sexual initiator of the groom (and the bride) played by the godfather on the wedding night. The data have miraculously survived (as if they were "living fossils", as Mircea Eliade named them in an article from 1939) in Romanian folk proverbs, in ritualistic customs from the traditional wedding ceremony, in folk ballads etc.